A New Measurement Scale for Evaluating Health-Related Quality of Life in Men with Prostate Cancer - hasan, ahmed; ali, abdulkhaliq (Iraqi National Journal of Nursing Specialties, 2017)
Objectives: This study aimed to identify and study most properties of the specific and general health-relatedquality-of-life (HRQoL) in prostate cancer patients, as well as creating a new measurement scale for assessing QoLamong prostate cancer patients.Methodology: A cross sectional (descriptive) study was conducted to evaluate General Quality of life in patientswith prostate cancer. A sample of 100 prostate cancer patients from Al-Amal National hospital for cancermanagement and Oncology Center in Baghdad Medical City. This study applied format of General World HealthOrganization Quality of Life-BERF questionnaire. The methods used descriptive statistics to evaluate the GeneralQoL-Improvements, as well as inferential statistical methods were used such that (Wilcoxon Signed Rank,McNemar).Results: Patients with prostate cancer have different assessment concerning general QoL, and have instability oftheir daily life cycle, within a moderate level. Regarding Specific QoL, overall result showed moderate assessmentof quality of life,nbut some domains showed worse assessment than others specially (sexual confidence, sexualintimacy and prostate specific antigen (PSA) concern domains). Other domains accounted moderate responses andthose were (urinary control, masculine and self-esteem, heath worry, cancer control, informed decision and outlook),while (marital affection, sexual intimacy and regret) accounted high responding, therefore, prostate cancer patientshave instability of their daily life cycle, within a moderate level. A new measurement scale was created using factoranalysis technique on WHO HRQoL BREF and specific HRQoL of prostate cancer patients